Maternal survival costs in an asocial mammal. Issue 5 (11th May 2022) - Kanaziz, Rachel; Huyvaert, Kathryn P.; Wells, Caitlin P.; Van Vuren, Dirk H.; Aubry, Lise M.
Abstract: Maternal characteristics, social dynamics, and environmental factors can all influence reproduction and survival and shape trade‐offs that might arise between these components of fitness. Short‐lived mammals like the golden‐mantled ground squirrel (GMGS; Callospermophilus lateralis ) tend to maximize effort toward current reproduction at the expense of survival but may be complicated by other aspects of the species' life history and environment. Here, we use 25 years of data (1995–2020) collected from a population of GMGS at the Rocky Mountain Biological Research Laboratory in Gothic, Colorado, to test the effect of several maternal characteristics (e.g., age, experience, and timing of litter emergence), social context (e.g., litter sex ratio and kin density), and environmental context (e.g., date of bare ground and length of vegetative growing season) on survival of reproductive female GMGS using Cox proportional hazard models. Our results indicated that social dynamics (i.e., density) and environmental conditions (i.e., standardized first day of permanent snow cover and length of growing season) explained significant variation in annual maternal survival, while maternal characteristics did not. A higher density of related breeding females and the total number of females (both related and unrelated to the focal mother) were associated with an increase in the mortality hazard. A later standardized date of the first day of permanent snow cover and a shorter growing season both reduced the maternal mortality hazard. Together, our results suggest that factors extrinsic to the squirrels affect maternal survival and thus may also influence local population growth and dynamics in GMGS and other short‐lived, territorial mammal species. Abstract : We used 25 years of longitudinal data collected from golden‐mantled ground squirrel females to test the effects of individual characteristics, the social context, and the environment on female mortality using Cox proportional hazard models. Both female kin density and the environmental context explained significant variation in female mortality, while individual characteristics did not. Our results suggest that both kin density and climate metrics related to growing season phenology swamp individual characteristics in explaining variability in maternal mortality. This is an important finding in a rather short‐lived species where every additional active season survived has a lot of weight in improving lifetime reproduction.